PENGARUH MEDIA PEMBELAJARAN SAINS TERHADAP KEMAMPUAN KOGNITIF ANAK DI TK MUTIARA LAUT DESA OLUHUTA KECAMATAN KABILA BONE KABUPATEN BONE BOLANGO - Bidi, Ulan (Almeera Education, 2023)
Introduction to science should be done from an early age with fun activities and through habituation so that children experience the science process directly. This is done so that children not only know the results but can also understand the process of the science activities they do. This study aims to determine the effect of science learning media on children's cognitive abilities at Mutiara Laut Kindergarten, Oluhuta Village, Kabila Bone sub-district, Bone Bolango district. The research method used in this research is an experimental method that is carried out to determine the effect given to the experimental class. This research is planned to be carried out at Mutiara Laut Kindergarten, Oluhuta Village, Kabila Bone District, Bone Bolango Regency. The data collection techniques used are observation, questionnaire, and documentation. based on the results of the research that has been discussed in the discussion above, it can be concluded that there is an effect of simple science learning methods on the cognitive abilities of children aged 4-5 years, as evidenced by the normality test of the pretest results of 0.757, then the normality test of the posttest results of 0.147. For hypothesis testing, the results of t count are 39.528 and t table 2.1009. These results show t count> t table with α 0.05, which means the hypothesis Ha is accepted and Ho is rejected.